Nutritional composition of three grasses from the state of Morelos, Mexico - Sosa-Montes, Eliseo; Mendoza-Pedroza, Sergio Iban; Ramos-Velázquez, Andrés; Alvarez- Vázquez, Perpetuo; Ortega- Jiménez, Eusebio; Sánchez- Hernández, Miguel Angel (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this study was to evaluate the chemical composition and in vitro digestibility of three forage grasses, Bromus diandrus, Oplismenus burmannii and Heteropogon contortus, subfamilies Pooideae, Pooideae and Panicoideae, respectively. The main response variables, all on dry basis were: ashes (Ash), crude protein (CP), ether extract (EE), soluble carbohydrates (SC), neutral detergent fiber (NDF), cell content (CC = 100 - FDN) and in vitro dry matter digestibility (IVDMD). Each grass was evaluated in triplicate and one replicate was considered the experimental unit. Means were separated using the Tukey test (p < 0.05). The association between each pair of variables (p < 0.05) was estimated by the Pearson correlation coefficient (p < 0.05). The grasses B. diandrus and O. burmannii showed (p < 0.05) more CP, CC and IVDMD as well as less cell wall or NDF (insoluble component) than H. contortus. This produced a positive correlation between CC and CP (0.751 p < 0.05). Additionally, O. burmannii produced the highest value of Ash and the lowest of SC, while B. diandrus showed the lowest value of Ash and the highest of SC (p < 0.05). This produced a negative correlation between Ash and SC (-0.976, p < 0.01). In conclusion, the grass B. diandrus, showed better chemical composition and digestibility than the other two, so this grass is recommended for ruminant nutrition.